2011
DOI: 10.4061/2011/696942
|View full text |Cite
|
Sign up to set email alerts
|

Production of Xylanase fromArthrobactersp. MTCC 6915 Using Saw Dust As Substrate under Solid State Fermentation

Abstract: Saw dust was used as substrate for xylanase production from Arthrobacter sp. MTCC 6915. The study of period of incubation, temperature, pH, carbon, and nitrogen sources for xylanase production was optimized. Xylanase production was found to be optimum at an incubation period of 96 hrs (117.0 U/mL), temperature 30°C (105.0 U/mL), and pH 9.0 (102.9 U/mL). The results showed that the xylanase production was found to be higher in the presence of carboxymethylcellulose (176.4 U/mL) and dextrose (126.0 U/mL). It was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 32 publications
4
12
0
4
Order By: Relevance
“…Sepahy et al [52] reported a fermentation period of 48 h by Bacillus mojavensis AG137 in submerged fermentation using oat bran as a substrate. Murugan et al [72] reported 96 h as optimum fermentation period for xylanase production by Arthrobacter sp. MTCC 6915 in SSF using sawdust as a substrate.…”
Section: Discussionmentioning
confidence: 99%
“…Sepahy et al [52] reported a fermentation period of 48 h by Bacillus mojavensis AG137 in submerged fermentation using oat bran as a substrate. Murugan et al [72] reported 96 h as optimum fermentation period for xylanase production by Arthrobacter sp. MTCC 6915 in SSF using sawdust as a substrate.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, various agro-industrial waste materials like corn meal, corn cob, wheat bran, wheat straw, rice straw, sugarcane bagasse and coffee by-products are being used as substrates for the production of fungal xylanases (MURUGAN et al, 2011). Brewer's spent grain (BSG) is the main residue of brewing industry, representing around 85% of total by products generated (ALIYU; BALA, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Besides minimising the expensive costs of pure xylan and reducing the costs of dewatering system, SsF with agricultural residuals as the carbon source would remarkably result in the shortest production time possible and thus, lessen the risk of contamination, making SsF, a promising technology for xylanase production in the future. Interestingly, based on our findings, the maximum xylanase synthesis of 8.6382 U/ml was attained in the shorter fermentation time of 48 h under SsF compared to other studies which required 96 h of SsF for the maximum production of xylanase by Arthrobacter spp [63].…”
Section: Medium Ph Profile From Various Nitrogen Concentrationsmentioning
confidence: 68%